Developing a monograph book for teaching English skills to young learners in wetlands areas - Dini Noor Arini; Raisa Fadilla (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
To enable Universitas Lambung Mangkurat (ULM) to become the Asia-Pacific centre for wetlands development in 2027, one of the efforts ULM makes is to raise awareness about the importance of optimising human resources in wetlands through research and development in the educational and cultural fields. English is considered a foreign language in Indonesia, allowing students to use the language outside of academic settings. English becomes a required subject in junior and senior high school; however, the government requires that English be taught in primary schools as a local topic. English, on the other hand, remains a mandatory subject in a large number of Indonesian primary schools, particularly in Banjarmasin. The issue arises in primary school English instruction because there is no clear guidance for teachers on how to teach English in an appropriate and engaging manner for the students. Due to the absence of a monograph book on teaching methods, teachers in some primary schools in Banjarmasin, particularly those located in wetland areas, have limited access to teaching English to young learners (EYL). In light of the university's policy and the critical nature of achieving teaching and learning objectives, as well as the absence of a suitable reference book for teaching EYL, this study aims to develop an appropriate monograph book on teaching techniques for students of young ages. The research and development design is chosen because it aims to create a product and meets the needs of the reference book's development. The results are expected to improve students' academic performance and to assist EYL teachers in wetland areas in conducting effective and meaningful teaching.